Requiem for Battleship Yamato - Yoshida, Mitsuru; Minear, Richard H. (Annapolis, Maryland : Naval Institute Press, 1999)
A young ensign on the bridge of the fabled battleship Yamato during her final battle, recounts his experience.
The Breakup of the Task ForceThe Fateful Moment; Last Dispositions; Escape from the Bridge; The Great Whale Sinks; Explosion; Adrift; Rescue; The Remnants of the Task Force; Tales Told by Some of Those Rescued; Safe Return; Some Reflections.
English.
Online resource; title from digital title page (viewed on August 28, 2020).
Keywords: Yoshida, Mitsuru; Yoshida, Mitsuru; Yamato (Battleship); Yamato (Battleship); 1939-1945; World War, 1939-1945 -- Naval operations, Japanese; World War, 1939-1945 -- Personal narratives, Japanese; HISTORY -- Europe -- Western; Military operations, Naval -- Japanese; Personal narratives; Personal narratives -- Japanese; Personal narratives; 2